Republic of Madagascar : Staff-Monitored Program and Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Madagascar's Staff-Monitored Program (SMP) and Request for Disbursement under the Rapid Credit Facility (RCF). Madagascar's economic recovery has failed to gain momentum in 2015, largely due to external shocks, persistent political instability, and weak governance. Nonetheless, the authorities have implemented an adequate policy mix that has broadly maintained macroeconomic stability. In light of urgent balance of payments needs, the Malagasy authorities are requesting a second disbursement under the RCF, accompanied by a SMP. The IMF staff supports the authorities' request for a disbursement under the RCF based on the policy track record over the past six months.